2014
DOI: 10.3892/mmr.2014.2985
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord-derived mesenchymal stem cell therapy for neurological disorders via inhibition of mitogen-activated protein kinase pathway-mediated apoptosis

Abstract: The present study investigated the recovery and intrathecal administration of human umbilical cord‑derived mesenchymal stem cells (HUC‑MSCs) by lumbar puncture and analyzed the technical difficulties and short and long‑term effects of UC‑MSC transplantation in various neurological conditions. In total, 100 patients who underwent subarachnoid placement of UC‑MSCs between December 2006 and May 2010 were included in the present study. The present study evaluated the number of attempts, localization of subarachnoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…At the same time, Bcl2 expression increased, whereas Bax expression decreased following stem cell transplantation. There are also data indicating that transplantation of MSCs for neurological disorders inhibited apoptosis and the protein expression of c-Jun N-terminal kinase and p38 as well triggered the phosphorylation of P-42/44 ERK1/2 [130]. However, it remains undetermined whether MAPK/ERK1/2-cascade participates in other mechanisms beyond inhibition of apoptosis, such as secretion of various neurotrophic factors that promote the regeneration or improving the axon regeneration microenvironment.…”
Section: Molecular Mechanisms After Msc Transplantation For Scimentioning
confidence: 99%
“…At the same time, Bcl2 expression increased, whereas Bax expression decreased following stem cell transplantation. There are also data indicating that transplantation of MSCs for neurological disorders inhibited apoptosis and the protein expression of c-Jun N-terminal kinase and p38 as well triggered the phosphorylation of P-42/44 ERK1/2 [130]. However, it remains undetermined whether MAPK/ERK1/2-cascade participates in other mechanisms beyond inhibition of apoptosis, such as secretion of various neurotrophic factors that promote the regeneration or improving the axon regeneration microenvironment.…”
Section: Molecular Mechanisms After Msc Transplantation For Scimentioning
confidence: 99%
“…In a study comparing mesenchymal stem cells derived from fat, bone marrow, Wharton's jelly and umbilical cord blood for treating spinal cord injuries, dogs have been treated with only matrigel or matrigel mixed with each type of mesenchymal stem cells. Although there have been no significant differences in functional recovery among the mesenchymal stem cell groups, application of umbilical cord stem cells has led to more nerve regeneration, neuroprotection and less inflammation compared to other mesenchymal stem cells [115].…”
Section: The Ideal Source For Mesenchymal Stem Cellsmentioning
confidence: 94%
“…Placental mesenchymal stromal cells have rescued ambulation in ovine myelomeningocele [150]. Umbilical cord-derived mesenchymal stem cell therapy for neurological disorders may act via inhibition of mitogen-activated protein kinase pathwaymediated apoptosis [115]. Through the effect on glial cells(suppression of activated astrocytes and microglia), proinflammatory (Interleukin-1β and Interleukin-17A) and anti-inflammatory cytokines (anti-inflammatory cytokine Interleukin-10), intrathecal injection of human umbilical cord-derived mesenchymal stem cells has ameliorated neuropathic pain in rats [151].…”
Section: Peculiarities Of Human Umbilical Cord Blood-derived Mesenchymentioning
confidence: 99%
“…In 2013, Yao et al 95 reported improved autonomic function and somatosensory evoked potentials 12 months after intrathecal and intravenous injection of UCB-MNCs into 25 patients with chronic SCI (≥6 months). Several groups transplanted umbilical cord-derived mesenchymal cells intrathecally into patients with SCI 9698 .…”
Section: Introductionmentioning
confidence: 99%
“…In the phase II trial in KM, 20 patients with chronic (average of 7 years after injury) complete C5–T11 SCI were sequentially assigned to five treatment groups in which they received 1.6 (group A), 3.2 (group B), or 6.4 (group C) million UCB-MNCs, 6.4 million UCB-MNCs with a 30-mg/kg bolus dose of MP (group D), or 6.4 million UCB-MNCs with MP and a 6-week course of oral lithium carbonate (group E). The patients then started 3–6 months of intensive locomotor training and were assessed at 6 weeks, 3 months, 6 months, and about 1 year after surgery for changes in the American Spinal Injury Association and International Spinal Cord Society (ASIA/ISCOS) impairment scale (AIS) classification 97–100 , motor and sensory scores, the walking index of spinal cord injury (WISCI) 99104 , the spinal cord independence measures (SCIM III) 105107 , modified Ashworth scale (MAS) for spasticity 108118 , visual analog scale (VAS) for pain, and severe adverse events (SAEs).…”
Section: Introductionmentioning
confidence: 99%